Estimation of Marine Macroalgal Biomass Using a Coverage Analysis - Seung Wook Jung; Chang Geun Choi (Journal of Marine Science and Engineering, 2022)
This study was conducted to assess the feasibility of biomass estimation by non-destructive sampling, determine whether the results derived from various types of marine macroalgae are reliable, and a newly proposed method. A quantitative survey was conducted on marine macroalgae communities distributed in the subtidal zone in 67 coastal regions in Korea. Regression analyses were conducted on 11,642 fresh weight datasets covering of 135 species of marine macroalgae. The linear function was FW = 17.721C (adj r2 = 0.745, p < 0.001) and the power function was FW = 4.48C1.251 (adj r2 = 0.891, p < 0.001). Our analysis accounted for the fact that there were three vertically distributed layers of a marine macroalgal assemblages with various shapes (i.e., the Ecklonia complex, the Sargassum and Undaria complex, and the understory complex). For the Ecklonia complex, the linear function was FW = 27.360C (adj r2 = 0.886, p < 0.001) and the power function was FW = 9.626C1.223 (adj r2 = 0.909, p < 0.001). For the Sargassum and Undaria complex, the linear function was FW = 18.389C (adj r2 = 0.916, p < 0.001) and the power function was FW = 6.567C1.255 (adj r2 = 0.942, p < 0.001). For the understory complex, the linear function was FW = 10.419C (adj r2 = 0.737, p < 0.001) and the power function was FW = 4.377C1.182 (adj r2 = 0.871, p < 0.001). Our findings demonstrated that the proposed method can accurately estimate the primary productivity of a wide range of coastal ecosystems based on remote sensing and non-destructive surveys of small-scale marine macroalgal communities.